2016
DOI: 10.1093/beheco/arw064
|View full text |Cite
|
Sign up to set email alerts
|

Sexually selected sentinels? Evidence of a role for intrasexual competition in sentinel behavior

Abstract: Lay SummaryFew studies have considered whether competition between members of the same sex has shaped the expression of cooperative behaviors. Here, we provide experimental evidence that sentinel behavior plays a role in defense against same-sex competitors. Song playbacks that simulated male intrusions elicited a marked increase in sentineling by the dominant male, and also suggested that the sentinel position itself may facilitate the initiation of anti-intruder responses.Twitter: @Linds__Walker @animalsocie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…Young). Reproduction within the group is monopolized by a single dominant pair (Harrison, York, Cram, Hares, et al, ; Harrison, York, Cram, & Young, ) while subordinate group members contribute to a range of cooperative activities including feeding nestlings (Cram, Blount, & Young, ; Walker, York, & Young, ). Throughout the breeding season (October to April inclusive), all nests were closely monitored to attain lay and hatch dates for all eggs.…”
Section: Methodsmentioning
confidence: 99%
“…Young). Reproduction within the group is monopolized by a single dominant pair (Harrison, York, Cram, Hares, et al, ; Harrison, York, Cram, & Young, ) while subordinate group members contribute to a range of cooperative activities including feeding nestlings (Cram, Blount, & Young, ; Walker, York, & Young, ). Throughout the breeding season (October to April inclusive), all nests were closely monitored to attain lay and hatch dates for all eggs.…”
Section: Methodsmentioning
confidence: 99%
“…Animal sentinel behaviour has been widely studied in many species of mammals, birds and even fish (reviewed by [15]). As can be imagined, many of them are cooperative breeders, such as jungle babblers, Turdoides striatus [1], pied babblers, Turdoides bicolor , [16,17], Arabian babblers, Turdoides squamiceps [5], Florida scrub jays, Aphelocoma coerulescens [4], white-browed sparrow weavers, Plocepasser mahali [18,19], dwarf mongooses, Helogala parvula [2,14] and meerkats, Suricata suricatta [20]. …”
Section: Introductionmentioning
confidence: 99%
“…In the pied babbler, the time is about 30% [16]. White-browed sparrow weaver groups have a sentinel about 21% of the time [19]. In the Florida scrub jay, groups were guarded by at least one sentinel about 33% in late summer, 50% in spring and about 75% in winter [4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies compared sentinel durations of dominants and subordinates in cooperative breeders. In the Arabian babbler, Turdoides squamiceps (Wright, Berg, Kort, Khazin, & Maklakov, 2001a;Wright et al, 2001b), Florida scrub-jay, Aphelocoma coerulescens (Bednekoff & Woolfenden, 2003, 2006, pied babblers, Turdoides bicolor (Hollen et al, 2011), white-browed sparrow weaver, Plocepasser mahali (Walker, York, & Young, 2016) and meerkats, Suricata suricatta (Clutton-Brock et al, 1999), dominants act as sentinels significantly more than subordinates. In dwarf mongoose, Helogale undulata, Rasa (1986) found that subordinates sentinel more than dominants, but these findings were overturned in Kern, Sumner, and Radford (2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the Arabian babbler, Turdoides squamiceps (Wright, Berg, Kort, Khazin, & Maklakov, 2001a;Wright et al, 2001b), Florida scrub-jay, Aphelocoma coerulescens (Bednekoff & Woolfenden, 2003, 2006, pied babblers, Turdoides bicolor (Hollen et al, 2011), white-browed sparrow weaver, Plocepasser mahali (Walker, York, & Young, 2016) and meerkats, Suricata suricatta (Clutton-Brock et al, 1999), dominants act as sentinels significantly more than subordinates. In the Arabian babbler, Turdoides squamiceps (Wright, Berg, Kort, Khazin, & Maklakov, 2001a;Wright et al, 2001b), Florida scrub-jay, Aphelocoma coerulescens (Bednekoff & Woolfenden, 2003, 2006, pied babblers, Turdoides bicolor (Hollen et al, 2011), white-browed sparrow weaver, Plocepasser mahali (Walker, York, & Young, 2016) and meerkats, Suricata suricatta (Clutton-Brock et al, 1999), dominants act as sentinels significantly more than subordinates.…”
mentioning
confidence: 99%